Pengaruh Sosialisasi Perpajakan, Kualitas Pelayanan Fiskus dan Sanksi Perpajakan Terhadap Kepatuhan WPOP: Bahasa Indonesia - Nelly, Nelly; Wangdra, Ronald (Owner : Riset dan Jurnal Akuntansi, 2024)
Taxes are mandatory contributions from the people as taxpayers to the state treasury based on established law. 79% of state revenue comes from taxes and is included in the state budget. Which is with the intention to spend on public needs. This research is aim to to test whether there is an effect of Tax Socialization, Quality of Fiscal Services and Tax Sanction on WPOP compliance. This study has a population 75,350 Individual Taxpayer Registered at KPP Pratama South Batam. Sampling used simple random sampling method and obtained a sample of 111. The data source was primary data through distributed questionnaires. The data analysis technique used to conduct this research was multiple linear regression analysis. However, because there is heteroskedasticity, the researcher uses Parameter Estimates with Robust Standard Errors as a benchmark in determining significance Based on the tests conducted in this study, it was concluded through the T test and F test that Tax Socialization has no effect on Individual Taxpayer Compliance, Fiscal Service Quality has no effect on Individual Taxpayer Compliance. And also Tax Sanctions have a positive significant effect on Individual Taxpayer Compliance. Meanwhile, the coefficient of determination shows that Individual Taxpayer Compliance is influenced by an independent variable of 41,7%. While the remaining 58,3% is influenced by other independent variables that not tested in this study.